The modeling of the interaction of pulsed 5G/6G signals and the fine structure of human skin - Noa Betzalel; Yuri Feldman; Paul Ben Ishai (Scientific Reports)
Abstract Current regulations concerning the allowed levels of human exposure to electromagnetic radiation emanating from wireless technologies are governed by the Specific Absorption Rate standard (SAR). This allows the absorption by tissue of up to 2 W/kg averaged for 6 minutes in a 10 g cube of homogenized tissue. Much criticized, the SAR standard relates only to thermal effects. However, with the advent of 5G and 6G technologies, exploiting frequencies above 4 GHz, the traditional methods of SAR measurement are proving to be inadequate. This is made more poignant as carrier wavelengths approach the dimensions of tissue structures. We present a detailed electromagnetic simulation of human skin that not only accounts for the multi-layered structure of skin, but also sweat ducts, capillaric and arterial blood vessels. The results show an inhomogeneous absorption pattern that reflects the vessels and sweat glands involved. As human skin hosts an array of sensing structures, from nociceptors to thermoreceptors, as well as millions of innervated sweat glands, we point out that the current methods for gauging the SAR rating of devices are wholly inadequate and may lead to a gross underestimation skin electromagnetic absorption, and that nerve excitation should be accounted for in risk assessment.